Performance and Tracking Efficiency of Exchange Traded Funds : An Analysis of Indian Equity Index Funds - Saji, T. G. (Indian Journal of Research in Capital Markets, 2017)
This research, using daily closing values of five leading Nifty exchange traded funds (ETFs), sought empirical evidence for the efficiency of equity ETFs in India to track their benchmark index. The study computed ’standard deviation of differential returns’ and ’standard error in regressing the fund return against the Nifty return’ to assess the tracking efficiency of funds. The analysis found underperformance of Nifty ETFs relative to their benchmark index coupled with higher level of tracking errors during market downturns. In contrast, I found significant improvement in tracking ability and most funds outperformed the benchmark with lower tracking errors under reverse market conditions. The research ultimately suggested that preferring ETFs to index portfolio investing offered greater opportunities for arbitrage to the investors of emerging markets like India, particularly during the times of market buoyancy.